2019
DOI: 10.1016/j.ejso.2019.07.017
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneous radiological response to neoadjuvant therapy is associated with poor prognosis after resection of colorectal liver metastases

Abstract: a b s t r a c tIntroduction: Surgery combined with perioperative chemotherapy has become standard of care in patients with resectable colorectal liver metastases. However, poor outcome is expected for a significant subgroup. The clinical implications of inter-metastatic heterogeneity remain largely unknown. In a prospective, population-based series of patients undergoing resection of multiple colorectal liver metastases, the aim was to investigate the prevalence and prognostic impact of heterogeneous response … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 40 publications
3
10
0
Order By: Relevance
“…In our study, heterogeneous radiological response to a targeted therapy was observed in nine of 38 (24%) patients, more than twice the rate reported in the literature for response to chemotherapy, 5,6 and definitely in contrast to the homogeneous pattern of response recently reported in mismatch repair deficiency CRC patients treated with immunotherapy 28 . Lesion specific response has been previously documented in patients treated for lmCRC with targeted agents 7,29,30 .…”
Section: Discussionsupporting
confidence: 64%
See 2 more Smart Citations
“…In our study, heterogeneous radiological response to a targeted therapy was observed in nine of 38 (24%) patients, more than twice the rate reported in the literature for response to chemotherapy, 5,6 and definitely in contrast to the homogeneous pattern of response recently reported in mismatch repair deficiency CRC patients treated with immunotherapy 28 . Lesion specific response has been previously documented in patients treated for lmCRC with targeted agents 7,29,30 .…”
Section: Discussionsupporting
confidence: 64%
“…This phase II trial showed clinical benefit from treatment in 70% of patients 3 . Unfortunately, as we and others have shown, patients may exhibit a heterogeneous response, some metastases shrinking while others are progressing 4‐6 . Kessel et al 5 have also shown that heterogeneous response, caused by the onset of new resistant tumor clones in some lesions, is a predictor of poor overall survival 7,8 .…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation
“…We have also demonstrated that intermetastatic heterogeneity in response to neoadjuvant treatment will be associated with poor survival after resection of CRLMs. 47 This response heterogeneity was not explained by the heterogeneity in these driver genes, indicating that several aspects of heterogeneity can be associated with disease behavior and prognosis.…”
Section: Discussionmentioning
confidence: 97%
“…The clinical impact of such intermetastatic molecular heterogeneity remains poorly defined [22,23,26], although our study suggested that a high degree of heterogeneity of DNA copy number aberrations (CNAs) is associated with a poor prognosis [25]. We have previously also reported differential radiological responses to standard neoadjuvant treatment among metastatic lesions in a subgroup of approximately 10% of patients with resectable CRLM [27]. How this phenotypic heterogeneity relates to molecular heterogeneity is currently not clear, but the poor survival rate of this patient subgroup after surgery highlights the potential clinical importance of intermetastatic heterogeneity.…”
Section: Introductionmentioning
confidence: 97%